String Processing and Information Retrieval 17th International Symposium, SPIRE 2010, Los Cabos, Mexico, October 11-13, 2010. Proceedings - Chavez, Edgar; Lonardi, Stefano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 17th International Symposium on String Processing and Information Retrieval, SPIRE 2010, held in Los Cabos, Mexico, in October 2010. The 26 long and 13 short papers presented were carefully reviewed and selected from 109 submissions. The volume also contains 2 invited talks. The papers are structured in topical sections on crowdsourcing and recommendation; indexes and compressed indexes; theory; string algorithms; compressions; querying and search user experience; document analysis and comparison; compressed indexes; and string matching.
Crowdsourcing and Recommendation -- Querying the Web Graph -- Incremental Algorithms for Effective and Efficient Query Recommendation -- Fingerprinting Ratings for Collaborative Filtering $1 (BTheoretical and Empirical Analysis -- On Tag Spell Checking -- Indexes and Compressed Indexes -- Compressed Self-indices Supporting Conjunctive Queries on Document Collections -- String Retrieval for Multi-pattern Queries -- Colored Range Queries and Document Retrieval -- Range Queries over Untangled Chains -- Theory -- Multiplication Algorithms for Monge Matrices -- Why Large Closest String Instances Are Easy to Solve in Practice -- A PTAS for the Square Tiling Problem -- On the Hardness of Counting and Sampling Center Strings -- String Algorithms I -- Counting and Verifying Maximal Palindromes -- Identifying SNPs without a Reference Genome by Comparing Raw Reads -- Dynamic Z-Fast Tries -- Improved Fast Similarity Search in Dictionaries -- Compression -- Training Parse Trees for Efficient VF Coding -- Algorithms for Finding a Minimum Repetition Representation of a String -- Faster Compressed Dictionary Matching -- Relative Lempel-Ziv Compression of Genomes for Large-Scale Storage and Retrieval -- Querying and Search User Experience -- Standard Deviation as a Query Hardness Estimator -- Using Related Queries to Improve Web Search Results Ranking -- Evaluation of Query Performance Prediction Methods by Range -- Mining Large Query Induced Graphs towards a Hierarchical Query Folksonomy -- String Algorithms II -- Finite Automata Based Algorithms for the Generalized Constrained Longest Common Subsequence Problems -- Restricted LCS -- Extracting Powers and Periods in a String from Its Runs Structure -- On Shortest Common Superstring and Swap Permutations -- Document Analysis and Comparison -- A Self-Supervised Approach for Extraction of Attribute-Value Pairs from Wikipedia Articles -- Temporal Analysis of Document Collections: Framework and Applications -- Text Comparison Using Soft Cardinality -- Hypergeometric Language Model and Zipf-Like Scoring Function for Web Document Similarity Retrieval -- Compressed Indexes -- Dual-Sorted Inverted Lists -- CST++ -- Succinct Representations of Dynamic Strings -- Computing Matching Statistics and Maximal Exact Matches on Compressed Full-Text Indexes -- The Gapped Suffix Array: A New Index Structure for Fast Approximate Matching -- String Matching -- Parameterized Searching with Mismatches for Run-Length Encoded Strings -- Fast Bit-Parallel Matching for Network and Regular Expressions -- String Matching with Variable Length Gaps -- Approximate String Matching with Stuck Address Bits -- Erratum -- Erratum to: Range Queries over Untangled Chains.s
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Optical pattern recognition; Bioinformatics; Computer Science; Information Storage and Retrieval; Computational Biology/Bioinformatics.; Data Mining and Knowledge Discovery; Database Management; Pattern Recognition; Multimedia Information Systems